2020
DOI: 10.1021/acsmaterialslett.9b00500
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Self-Assembly of Fully Zwitterionic Triblock Copolymers

Abstract: Zwitterionic polymers are a distinctive class of materials with unique physical and chemical properties. In this study, the synthesis of fully zwitterionic ABA triblock copolymers was achieved by controlled radical polymerization using two different zwitterionic monomers, sulfobetaine methacrylate (SBMA) and 2-methacryloyloxyethyl phosphorylcholine (MPC). Due to the strong tendency of the sulfobetaine groups to aggregate, the fully zwitterionic triblock copolymers demonstrated self-assembly as well as salt and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
(47 reference statements)
1
9
0
Order By: Relevance
“…In addition, polyelectrolytes with charged functional groups can strongly affect the electrochemical and mechanical properties of hydrogel electrolytes. , For instance, Huang et al reported a sodium polyacrylate (PANa) based polyelectrolyte with a superabsorbency of aqueous electrolytes for Zn-ion batteries owing to their highly charged COO – groups . The electrostatic interactions between the negatively charged acrylate groups of PANa and positively charged Zn ions formed a quasi-SEI layer to facilitate ion transport and inhibit Zn dendrites, thus improving cycling stability for over 10 000 cycles.…”
Section: Hydrogel-based Materials In Energy Storage Applicationsmentioning
confidence: 99%
“…In addition, polyelectrolytes with charged functional groups can strongly affect the electrochemical and mechanical properties of hydrogel electrolytes. , For instance, Huang et al reported a sodium polyacrylate (PANa) based polyelectrolyte with a superabsorbency of aqueous electrolytes for Zn-ion batteries owing to their highly charged COO – groups . The electrostatic interactions between the negatively charged acrylate groups of PANa and positively charged Zn ions formed a quasi-SEI layer to facilitate ion transport and inhibit Zn dendrites, thus improving cycling stability for over 10 000 cycles.…”
Section: Hydrogel-based Materials In Energy Storage Applicationsmentioning
confidence: 99%
“…2c). 50 The fully ZI-ABA triblock polymers were synthesized through free radical polymerization with MPC as the middle block, and SBMA as the symmetrical end blocks. The ZI-ABA copolymers exhibit self-assembly behavior, and thermal- and salt-responsive behavior in solution due to the strong aggregation of SBMA.…”
Section: Zwitterionic-based Topological Polymersmentioning
confidence: 99%
“…31 Nevertheless, the phase behavior of polyzwitterion-containing BCPs lacks in-depth research. [32][33][34] In our previous work, high χ-low N BCPs with thermally stable sub-5 nm microdomains have been fabricated via polyzwitterion-containing BCPs. 35 Crosslinking-induced self-aggregation plays a key role in the strong incompatibility between polyzwitterions and the other block.…”
Section: Introductionmentioning
confidence: 99%